Digital health communications - Cordelier, Benoit, 1974-; Galibert, Olivier, 1973- (London : ISTE, Ltd. ; Hobooken : Wiley, 2021)
There are many controversies with respect to health crisis management: the search for information on symptoms, misinformation on emerging treatments, massive use of collaborative tools by healthcare professionals, deployment of applications for tracking infected patients. The Covid-19 crisis is a relevant example about the need for research in digital communications in order to understand current health info communication. After an overview of the challenges of digital healthcare, this book offers a critical look at the organizational and professional limits of ICT uses for patients, their caregivers and healthcare professionals. It analyzes the links between ICT and ethics of care, where health communication is part of a global, humanistic and emancipating care for patients and caregivers. It presents new digitized means of communicating health knowledge that reveal, thanks to the Internet, a competition between biomedical expert knowledge and experiential secular knowledge
BIBINDX
Keywords: Communication in medicine; Electronic books